(untitled) (Eurasian Journal of Physics,Chemistry and Mathematics, 2023)
Improving the effectiveness of physics teaching is an urgent problem of today. An approach to assessing the acquisition of new physical knowledge, which is a system of criteria levels, where the transition to each subsequent level is possible only if the previous one is available. A method of teaching experimental activity to students in physics based on the implementation of the system-activity approach with the help of a school physical experiment is offered. The main thing is the activity of methodology students in mastering not only the content, but also the process of acquiring new knowledge.